Qua Vadis Pendidikan Agama Islam Berbasis Multikulturalime di Indonesia - Rosady, Imron (Islam & Contemporary Issues, 2022)
This study examines topics relating to Islamic religious education using research in education that is multicultural in nature. The study of quo vadis Islamic Religious Education based on multiculturalism in Indonesia forms the basis of this research, which is based on a review of the relevant literature. In order to respond to some of the research questions in this paper, this study employs a qualitative descriptive analytic methodology. First, how is Indonesia's understanding of Islamic religious education? Second, what does the term "multicultural education" mean? Third, how does multiculturalism fit within Indonesia's quid vadis of Islamic religious education? Utilizing a content analysis method, descriptive analysis will be used to describe the quintessence of Islamic religious education based on multiculturalism in Indonesia, as well as data on the concepts of Islamic religious education, education based on multiculturalism, and multiculturalism. Knowing the concepts of multiculturalism, qua vadis, and Islamic religious education are the outcomes of this research. The study of multicultural education in Indonesia serves as the foundation for Islamic religious education.